Age affects the dynamic interaction between kinematics and gait stability - Liang, Shengyun (Frontiers in Bioengineering and Biotechnology, 2024)
It is crucial to comprehend the interplay between the center of mass (CoM) and base of support (BoS) in elderly individuals' body movements, as it could have implications for fall prevention. The purpose of this study is to characterize age-related differences using the instantaneous location of the CoM and CoM velocity vector in relation to the dynamically changing BoS during walk. Thirty subjects participated in the experiments. Derivation formulas of feasible stability region and age-related statistical analyses were proposed. The stability margin and distance to centroid for elderly group were found to be significantly difference to the young group (p < 0.05). At heel strike, while the CoMv distance was similar for age-based groups (p > 0.05), older demonstrated a greater CoMv distance to the border than the younger at right limb, that suggesting age-related differences in momentum control. In addition, Bland-Altman analysis indicated the validity was substantial, making it feasible to capture stride-to-stride variability. The CoM trajectories and feasible stability region could provide a better understanding of human momentum control, underlying mechanisms of body instability and gait imbalance.